Dipotassium Glycyrrhizate Improves Intestinal Mucosal Healing by Modulating Extracellular Matrix Remodeling Genes and Restoring Epithelial Barrier Functions - Stronati, Laura; Palone, Francesca; Negroni, Anna; Colantoni, Eleonora; Mancuso, Anna Barbara; Cucchiara, Salvatore; Cesi, Vincenzo; Isoldi, Sara; Vitali, Roberta (Frontiers in Immunology, 2019)
Gut mucosal healing (MH) is considered a key therapeutic target and prognostic parameter in the management of inflammatory bowel disease (IBD). The dipotassium glycyrrhizate (DPG), a salt of the glycoconjugated triterpene glycyrrhizin, has been shown to inhibit the High Mobility Group Box 1 (HMGB1) protein, an allarmin strongly implicated in the pathogenesis of most inflammatory and auto-immune disorders. Here we discuss new insights on how DPG acts on MH comparing the acute phase and the recovery phase from experimental colitis in mice. We found that DPG strongly accelerates MH by differently regulating pro-inflammatory (CXCL1, CXCL3, CXCL5, PTGS2, IL-1β, IL-6, CCL12, CCL7) and wound healing (COL3A1, MMP9, VTN, PLAUR, SERPINE, CSF3, FGF2, FGF7, PLAT, TIMP1) genes as observed only during the recovery phase of colitis. Relevant issue is the identification of extracellular matrix (ECM) remodeling genes, VTN and PLAUR, as crucial genes to achieve MH during DPG treatment. Furthermore, a noticeable recovery of intestinal epithelial barrier structural organization, wound repair ability and functionality is observed in two human colorectal adenocarcinoma cell lines exposed to DPG during inflammation. Thus, our study identifies DPG as a potent tool for controlling intestinal inflammation and improving MH.